Carbon dioxide utilization for global sustainability : proceedings of the 7th International Conference on Carbon Dioxide Utilization, Seoul, Korea, 12-16 October 2003 /: proceedings of the 7th International Conference on Carbon Dioxide Utilization, Seoul, Korea, 12-16 October 2003. (2004) - Unknown
No abstract available